Community Perceptions of Forest-Based Ecosystem Services in Protected Forests under the Social Forestry Program in Kulon Progo - Prasetyo Nugroho; Wiyono; Silvi Nur Oktalina; Rochmad Hidayat; Probo Santoso; Jangkung Tri Atmojo; Favian Bagus Abhyasa; Ardhian Srihermawan; Ahwan Maulana Fauzul Ngadim; Angelita Putri Prabandari; Ririn Arinda; Salsabilla Sinta Jati (Universitas Gadjah Mada, 2026)
Social forestry programs offered a substantial opportunity to enhance local livelihoods and foster sustainable forest governance. However, empirical insights into the specific forest-based ecosystem services (FbES) most valued by adjacent communities remained limited. Therefore, this research aimed to investigate community perceptions of FbES across three social forestry groups located within protected areas in Kulon Progo, Indonesia. Based on 306 completed survey responses, perceptions across three FbES categories, including provisioning, regulating, supporting, and cultural services, were assessed. The results showed distinct patterns in service valuation, with provisioning services consistently rated as the lowest. This outcome might have reflected the restrictive regulatory environment in protected forests, which limited extractive use and shaped community interactions with forest resources. In contrast, regulating, supporting, and cultural services were consistently perceived as more valuable, suggesting an appreciation for the ecological stability and cultural identity forests provide. Variation among groups also pointed to the influence of local customs and differential access to forest benefits. These results outlined the inherent trade-offs between conservation imperatives and livelihood needs, and the importance of adaptive, locally responsive forest management. The present research advanced current understanding of socio-ecological dynamics in social forestry and strategies to strengthen community participation and equitable benefit-sharing frameworks.